The software cost estimation method based on fuzzy ontology - Przemysław Plecka; Krzysztof Bzdyra (Foundations of Management, 2014)
In the course of sales process of Enterprise Resource Planning (ERP) Systems, it turns out that the standard system must be extended or changed (modified) according to specific customer's requirements. Therefore, suppliers face the problem of determining the cost of additional works. Most methods of cost estimation bring satisfactory results only at the stage of pre-implementation analysis. However, suppliers need to know the estimated cost as early as at the stage of trade talks. During contract negotiations, they expect not only the information about the costs of works, but also about the risk of exceeding these costs or about the margin of safety. One method that gives more accurate results at the stage of trade talks is the method based on the ontology of implementation costs. This paper proposes modification of the method involving the use of fuzzy attributes, classes, instances and relations in the ontology. The result provides not only the information about the value of work, but also about the minimum and maximum expected cost, and the most likely range of costs. This solution allows suppliers to effectively negotiate the contract and increase the chances of successful completion of the project.
Keywords: 650; ERP; software cost estimation; metrics; fuzzy ontology; implementation; specification of requirements